RESEARCH OF A CAR COLLISION WITH AN OBSTACLE - Kabylbekov K.A; Abdrakhmanova Kh.K; Saidakhmetov P.A; Kedelbaev B.Sh; Issaev E.B (Academic Scientific Journal of Computer Science, 2019)
The article considers the calculation and visualization of collision of a car with an obstacle by using the Matlab software. It contains the formulation of the problem, car and obstacle models, modeling parameters (the mass of the car, the speed of the car, parameters of the suspension: width, height, profile) and mathematical model of the collision profile. There are the calculation and visualization of the profile of the road roughness. The m-file titled “polizei.m” is created for calculation and visualization of the car’s motion. Calculation results are presented in graphs of displacement around a vertical axis and speed along the vertical axis at a various mass of the car, coefficients of elasticity and damping of the suspension. There is also the discussion of the results of the calculation and visualization. The program allows making experiments with a change of width and height of roughness of the road, of the mass of the car, of suspension parameters.